English with an accent: language, ideology, and discrimination in the United States - Laurence, Elizabeth (Colombian Applied Linguistics Journal, 2013)
The inherent versatility exhibited in the various writing genres of talented linguist, Rosina Lippi-Green, is as remarkable as her seemingly random interest in quilting. Her ability to make connections with many things, in addition to fabric, is neither coincidental nor haphazard. It is far from surprising, therefore, that this independent scholar claiming “mixed European ancestry” utilizes three authorial guises: two for penning historical fiction and a third for academic writing endeavors, the most recent being English with an accent: Language, ideology, and discrimination in the United States. Extensive documentation and factual data are but two persuasive means of support she utilizes to focus on and convince readers that the power of language upon social structures, especially in the discrimination and subordination of others, remains more strongly embedded than most people realize.